Exfoliative Dermatitis - A Clinical Study - Nazeer Mohamed; Ganesh Kamath H; Shetty Narendra J; Nandakishore B (Wolters Kluwer Medknow Publications, 2002)
A total number of thirty cases of exfoliative dermatitis was taken up for clinical evaluation with particular emphasis on the cause of the disease and to study systemic involvement. Eczema (46.6%) was the most common cause followed by psoriasis (16.6%). Elderly males were commonly affected with a mean age of 50.9 years.